Predictors of hospital readmission among older adults with cancer. Issue 7 (September 2020) - Burhenn, Peggy; Sun, Can-Lan; Scher, Kevin S.; Hsu, Joyce; Pandya, Punita; Chui, Ching-Yi; Arsenyan, Anait; Mitani, Dale; Morrison, Rachel; Katheria, Vani; Hurria, Arti
Abstract: Objective: Older adults with cancer are at higher risk for costly and potentially dangerous hospital readmissions. Identifying risk factors for readmission in this population is important for future prevention of readmission. Materials and methods: Hospital discharges among patients ≥ 65 years with solid tumors on non-surgical services from 2006-2011 were reviewed in this matched case-control study. We abstracted patient/cancer characteristics; functional status; fall risk; chemotherapy line; comorbidities; laboratory values; discharge parameters; and miscellaneous information (Do Not Resuscitate Order, pain scores) from medical records. Conditional logistic regression was used for univariate and multivariable analysis. Results: This analysis included 184 case-patients readmitted within 30 days after discharge from the index admission and 184 sex- and age-matched control-patients discharged from index admission within three months of the cases with no readmission. Cases and controls had no differences in terms of primary cancer type, treatment, and index admission reason. Cases were more likely to have abnormal hemoglobin, albumin, sodium, and SGOT on discharge. Compared to those with ≤1 abnormal laboratory test, patients with 2 or more abnormal test results were 3 times more likely to be readmitted within 30 days. Conclusion: This study demonstrated that older adults with cancer who had at least 2 abnormal laboratory results (hemoglobin, albumin, sodium, and SGOT) at discharge were 3 times more likely to be readmitted within 30 days compared to those with ≤1 abnormal results. These laboratory values may be predictive of the risk of readmission, and should be monitored before discharge to potentially prevent readmission.